Professional development in social work: elderly care in Sweden and Denmark - Christensen, Jonas Mikael (Social Welfare: Interdisciplinary Approach, 2016)
The purpose of this article is to highlight and give reflections on elderly care in two welfare states, Sweden and Denmark, on the basis of the question: how can the elderly care profession be understood from a transnational perspective? The empirical data consists of a project, and the analysis is based on an ecological model. The main conclusion is that by focusing on societal and professional knowledge sharing from a regional perspective, we can develop our understanding of the driving forces behind access to knowledge, professional identity maintenance and the professional position of the elderly individual.
Keywords: development ecology; elderly care; profession; social work; transnational